Determinants of service quality in bureaucracy: Parkinson's theory at work - Beate Jochimsen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
Parkinson's law states that work expands to fill the time available for its completion and that the number of administrators in an office is bound to increase over time. An unique laboratory to test Parkinson's ideas are vehicle registration offices in Germany. Using their data we found empirical support for Parkinson's law: First, service quality is no better in offices that have more staff per case. Second, service quality is worse if the service procedure is disaggregated into multiple smaller sub-services. Third, the staff size is a convex function of the number of customers. These results are robust to specifications in various alternative models.
Keywords: H83; D02; C21; C41; 330; Bureaucracy; Parkinson's law; Waiting time; Service Quality; Queueing Theory; Bürokratietheorie; Kraftfahrzeug; Genehmigung; Dienstleistungsqualität; Deutschland